A Spatiotemporal Equilibrium Model of Migration and Housing Interlinkages - Wukuang Cun; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper develops and solves a spatiotemporal equilibrium model in which regional wages and house prices are determined jointly with location-to-location migration flows. The agent's optimal location choice and the resultant migration process are shown to be Markovian, with the transition probabilities across all location pairs given as non-linear functions of wage and housing cost differentials, endogenously responding to migration flows. The model can be used for the analysis of spatial distribution of population, income, and house prices, as well as for the analysis of the entire dynamic process of shock spill-over effects in regional economies through location-to-location migration. The model is estimated on a panel of 48 mainland U.S. states and the District of Columbia over the training sample (1976-1999) and is shown to fit the data well over the evaluation sample (2000-2014). The estimated model is then used to analyse the size and speed of spatial spill-over effects by computing spatiotemporal impulse responses of positive productivity and land-supply shocks to California, Texas, and Florida. The sensitivity of the results to migration elasticity, housing depreciation rate and local land supply conditions is also investigated.
Keywords: E00; R23; R31; 330; location choice; joint determination of migration and house prices; spatiotemporal impulse responses; land-use deregulation; counterfactual exercise; population allocation; productivity and land supply shocks; California; Texas and Florida